La ciudad restauradora - Villalpando-Flores, Arturo Eduardo (2024)
The symbiotic relationship between human beings and the environment has evolved in parallel, leaving its mark on the genetic structure of our species and the formulation of social statutes. This convergence is evident in the dynamics of modern life, the functional aspects, and the emotional anchors. Based on the postulates of environmental psychology and design proposals, this article presents a model called “restorative urbanism”, stating that proximity to urban nature is a critical element in the composition and design of urban environments, fostering better perceptions of external habitability and improving individual and collective well-being in biopsychosocial terms through the environmental restoration process, achieving urban-environmental and psychological sustainability. The importance of the proposal lies in its ability to question how the morphological characteristics of the sociophysical space influence the quality of the socioenvironmental, physical, and emotional relationships with the surrounding environment, especially in the face of urban, environmental, and climatic contingencies.